Summer airborne mycoflora of Timişoara (Romania) and relationship to meteorological parameters. Issue 6 (2nd November 2017) - Ianovici, Nicoleta
Abstract: The present aeromycological investigation was undertaken to study atmospheric fungal spores in Timişoara (western Romania). This study was carried out using a Hirst type volumetric sampler. The study revealed the existence of a rich airborne mycoflora. The atmospheric fungal spores were classified and evaluated into three groups ('major', 'minor' and 'sporadic') depending upon their catch percentage in the air. Cladosporium / Fusarium / Leptosphaeria -group, Alternaria, Helminthosporium airborne fungal spores and airborne fungal fragments regularly recorded (frequency 100% of days). Cladosporium accounted for 81.09% of the outdoor fungal spores. The airborne fungal fragments have been identified as abundant in our geographic area. Spearman's correlations were applied to meteorological parameters and airborne fungal spore concentrations. In addition, correlations were calculated between the fungal spore concentrations and the meteorological variables from the previous day. A total of eleven weather factors were selected for this investigation. Following Spearman's correlations, I identified two patterns of behaviour: most of the airborne fungal spores prefer cloudiness, lower near-surface soil temperature, lower atmospheric pressure, higher relative humidity and precipitation (pattern A) while other spore concentrations favour increased sunshine, higher near-surface soil temperature and dry conditions (pattern B). The behaviour of some fungal spores during the warm season has proven unclear (pattern C). This study demonstrates the need for investigations throughout the year and the evaluation with complementary statistical methods, regarding the correct interpretation of airborne mycoflora relationships with meteorological parameters.